On knowledge-based design science information system (DSIS) for managing the unconventional digital petroleum ecosystems - Nimmagadda, Shastri; Mani, N.; Reiners, Torsten (2018)
© Springer International Publishing AG, part of Springer Nature 2019. The unconventional digital petroleum ecosystems are associated with fractured reservoirs that are usually unpredictable, but can produce for longer periods depending on size of petroleum systems and basins. Currently, conventional reservoirs do produce oil & gas even without integrated workflows and solutions. The heterogeneity and multidimensionality of data sources at times can make the data documentation and integration complicated affecting the exploration and field development. We examine the conventional database technologies and their failures in organizing the data of unconventional digital ecosystems. Big Data driven intelligent information system solutions are needed for addressing the issues of complex data systems of unconventional digital ecosystems. Geographically distributed petroleum systems and their associated reservoirs too demand such integrated and innovative digital ecosystem solutions. We propose an innovative design science information system (DSIS), an integrated digital framework solution to explorers, dealing with unconventional fractured reservoirs. The integrated Big Data analytics solutions are effective in interpreting unconventional digital petroleum ecosystems that are impacted by shale prospect businesses worldwide.